RELATIONSHIP OF SCR, CME AND CORONAL SHOCK WAVES WITH THE PARAMETERS OF TYPE IV AND II SOLAR RADIO BURSTS - Isaeva, E. A. (Одеські астрономічні публікації, 2020)
ABSTRACT. This paper presents the results of a comparative analysis of the relationship between solar cosmic rays (SCR), coronal mass ejections (CME), and coronal shock waves (CSW) with the parameters of solar continual type IV radio bursts, as well as with the parame- ters of type II radio bursts. The sample under study con- tains 147 proton events accompanied by type IV continu- um radio bursts in the 25-15400 MHz range, type II radio bursts in the 25-180 MHz range, as well as CME and cor- onal shock waves. For the analysis, we used original rec- ords of solar radio emission at 8 fixed frequencies in the range 245-15400 MHz according to data from RSTN (Ra- dio Solar Telescope Network), original records of dynam- ic spectra from SRS (Solar Radio Spectrograph) in the range of 25-180 MHz, as well as original records intensity of the flux of SCR protons with proton energies in the range> 1-100 MeV according to data from the GOES spacecraft. A comparative analysis showed that the rela- tionship between the intensity of the SCR proton flux and the CME velocity is, on average, much stronger with the parameters of type IV radio bursts than with the parame- ters of type II radio bursts, which indicates the dominant role of the SCR acceleration process in the flare region, rather than shock waves. However, detailed studies of the fine structure of type II radio bursts have shown that there is a fairly strong relationship between the intensity of the flux of mean-relativistic protons I p and the frequency f min,1 at the fundamental harmonic (at the 1-st harmonic) at the time t min corresponding to the minimum relative distance b min between the harmonics of type II radio bursts. De- tailed studies of the fine structure of type II radio bursts have also shown that there is a strong relationship between the intensity of the SCR proton flux I p and parameter V II , which characterizes the displacement of the shock front with time t i in a narrow frequency range of 25-60 MHz.